Expert opinion on "Results of a pilot clinical trial of the safety and efficacy of an original glycoprotein IIb/IIIa receptor inhibitor drug in acute coronary syndrome" - S. Yu. Martsevich (Кардиоваскулярная терапия и профилактика, 2023)
.